Hounsfield unit for assessing asymmetrical loss of vertebral bone mineral density and its correlation with curve severity in adolescent idiopathic scoliosis - Cheng, Yunzhong; Yang, Honghao; Hai, Yong; Pan, Aixing; Zhang, Yaoshen; Zhou, Lijin (Frontiers in Surgery, 2022)
Background: Low bone mass concomitantly occurs in patients with adolescent idiopathic scoliosis (AIS) and can persist until skeletal maturity. The purpose of this study was to assess the asymmetrical loss of vertebral bone mineral density (vBMD) and its correlation with curve severity in patients with AIS using Hounsfield unit (HU) values measured from computed tomography (CT) scans. Methods: Ninety-three AIS patients were retrospectively recruited. The HU values of the vertebral body (VB-HU) and pedicle screw trajectory (PST-HU) were measured from 4 vertebrae above (Apex-4) to 4 below (Apex+4) the apical vertebra (Apex) of the major curve. The VB-HU and PST-HU at the UEV, Apex, and LEV within the concave and convex sides of the major and minor curves and stable vertebrae were obtained. Results: A significant correlation was found between the Cobb angle and VB-HU at the periapical levels of the major curve. VB-HU and PST-HU at periapical levels were significantly greater within the concavity than the convexity of both major and minor curves. The asymmetric ratios of VB-HU and PST-HU were significantly correlated with the major curve Cobb angle, peaked at the apex and gradually diminished from the apex to the end vertebrae. The asymmetrical loss of vBMD aggravated with the progression of curve severity, presenting as VB-HU significantly decreased within the convexity and insignificantly decreased within the concavity of the major curve. Conclusion: The asymmetrical loss of vBMD was associated with the progression of curve severity in AIS. For patients with severe AIS, distraction of the pedicle screws at the concave side should be a priority in correcting the major curve, and supplemental anchors as well as larger-sized screws should be placed within the convex side around the apex of the major curve to reduce the risk of screw loosening after surgery.